U.S. and Them : The Geography of Academic Research - Das, Jishnu; Do, Quy-Toan; Shaines, Karen; Srikant, Sowmya (Elsevier, 2013)
Using a database of 76,046 empirical economics papers published between 1985 and 2005, we report two associations. First, research output on a given country increases with the country's population and wealth, yielding a strong correlation between per-capita research output and per-capita GDP. Regressions controlling for data quality, governance and the use of English give an estimated research–wealth elasticity of 0.32; surprisingly, the U.S. is not an outlier. Second, papers written about the U.S. are 2.5 percentage-points more likely to be published in the top five economics journals after accounting for authors' institutional affiliations and the field of study. This is a large effect because only 1.5% of all papers written about countries other than the U.S. are published in first-tier journals. No similar premium for research on the U.S. is detected in second-tier general interest journals, where papers from the UK and Europe command a substantial premium instead.